(untitled) (Northern International Medical College Journal, 2015)
Background : Acute Renal Failure (ARF) is a life threatening condition causing significant morbidity and mortality in children. Many studies on adult ARF survivors showed that renal insufficiency persisted after an attack of ARF. Children may be more susceptible to this injury due to immaturity and ongoing growth of the kidney. Objective : This study was conducted to assess the renal functional reserve or detect any sign of renal injury in children after an episode of Acute Renal Failure Methods : This prospective study was carried out in the Renal and Dialysis unit, Dhaka Shishu Hospital in 2007, January . Thirty patients were enrolled in this study by searching data held in the study centre. Results : Thirty (30) patients were selected in this study. Among them 46.7% was in the group > 5-10 years, only 10.0% was in age group < 1 year and more than 10 years respectively. Male were 63.3%, female were 36.7%.Causes of acute renal failure were diarrhoea with dehydration 43.3%, septicaemia 20.0%, Haemolytic Uraemic Syndrome (HUS) 20%, Acute Glomerulo Nephrities (AGN) 10.0%, Henoch Schonlein Purpura ( HSP) 3.3% and hepato renal syndrome 3.3%. During follow up Glomerular Filtration Rate(GFR) of the patients were in stage 1 in 76.7% cases , 10.0% in stage 2, 6.7% in stage 3 stage and in stage 4 & 5 3.3% cases.23.3% patients were found with GFR between stage 2 to stage 5, who had ARF due to HUS and HSP. The incidence of hypertension and proteinuria was found in 13.3% cases of HUS. Conclusion : The progressive nature of acute renal failure which may cause chronic kidney disease is an important observation. Northern International Medical College Journal Vol.6(1) 2014: 15-17